Nonproteolytic ubiquitination regulates chromatin occupancy by the NCoR/SMRT/HDAC3 corepressor complex in MCF-7 breast cancer cells - Giulio Ferrero; Maria Dafne Cardamone; Francesca Luca; Eliot Bourk; Laura Ricci; Wen Liu; Yuan Gao; Giulia Burrone; Akhirah Muhammad; Stefanie Chan; Emma Smith; Ting-Yu Claire Fan; et al. (Proceedings of the National Academy of Sciences, 2025)
Tight regulation of gene expression is achieved through the coordinated action of transcription factors and cofactors that often can act as both repressors and activators in response to regulatory signals, with their activity modulated by context-specific signal transduction pathways that also impinge on their transient and cyclical recruitment to chromatin. However, the mechanisms underlying the intricate interplay between the regulatory strategies controlling cofactors’ activity and localization across subcellar domains remain poorly understood. Here, we investigated the role of G-Protein Pathway Suppressor 2 (GPS2), a transcriptional cofactor critical for maintaining cellular homeostasis via regulation of mitochondrial biogenesis, stress response, lipid metabolism, insulin signaling, and inflammation, in MCF-7 breast cancer cells. By integration of biochemical assays with genome-wide RNA sequencing and Chromatin immunoprecipitation-Seq analyses, we show that nuclear GPS2 is required for licensing histone deacetylase 3 recruitment to chromatin via restricted ubiquitination by tumor necrosis factor receptor-associated factor 6 (TRAF6), an E3 ubiquitin ligase previously shown to regulate the switch from repressive to activating functions of the nuclear receptor corepressor (NCoR)/silencing mediator of retinoic acid and thyroid hormone receptor (SMRT) complex and here unexpectedly found to translocate to the nucleus in response to IL-1β stimulation. Nuclear TRAF6 is recruited to chromatin via direct interaction with the corepressors NCoR/SMRT, and TRAF6-mediated ubiquitination of TGF-beta activated kinase 1 (MAP3K7) binding protein 2 (TAB2), a facultative component of the NCoR/SMRT complex, contributes to corepressor clearance from target regulatory regions. Together, these results reveal an exquisite mechanism for coordinating the local regulation of cofactor activity with proinflammatory signaling pathways.